DESAIN INVERS DECOUPLING PADA SISTEM MIMO 3×3 DENGAN PENGENDALI PID - Zahrotul Azizah (Universitas Mulawarman, 2022)
The processes in the industry are categorized into a multi-input multi-output (MIMO) system, which consists of many inputs and outputs where the variables in the process are interrelated with each other. The interaction causes the controller design to be difficult. Even very strong interactions can worsen the performance of the controller. One way to reduce interaction is to add decoupling to the control system. There are several kinds of decoupling, but inverse decoupling was chosen because it can reduce the interaction significantly. This study aims to add inverse decoupling to the MIMO system with a larger size, namely 3×3. Larger system sizes lead to more complicated decoupling calculations. PID controller and inverse decoupling scheme became the chosen control strategy. Shell Heavy Oil Fractionator (SHOF) by Garcia is used as an illustrative example of a 3×3 MIMO system to demonstrate the performance results against the proposed control scheme. Based on the simulation results, the IAE value with the addition of inverse decoupling is smaller than without decoupling.Keywords: inverted decoupling, MIMO 3×3, PID controller